Low frequency of skin cancers in vitiligo patients - Barbara Algiert; Anna Erkiert-Polguj; Agnieszka Dana; Dariusz Czubiński; Helena Rotsztejn (Termedia Publishing House, 2016)
Vitiligo is a disease characterized by discoloration of the skin and hair as a result of damage of melanocytes. The exact mechanism of the disease is still unknown. Theories about the pathogenesis focus on autoimmune, neurogenic and autocytotoxic mechanisms. There is a decreased risk of incidence of skin cancers in patients with vitiligo. The relation between vitiligo and decreased frequency of cases of malignant melanoma (MM) may be a consequence of the immune response to antigens, which are common for melanocytes and MM cells. Genetic studies indicate a mutually exclusive relationship of melanoma and vitiligo. This disease is also associated with a polymorphism in the TYR gene which encodes tyrosinase. Studies also indicate a decreased risk of incidence of nonmelanoma skin cancers (NMSC) in patients with vitiligo.